Smartphones and Mobile Apps: Case Study on Usage Behavior of Elementary School Students – Insights from a Rural Area in Northern Germany - Wohllebe, Atilla; Hübner, Dirk-Siegfried; Radtke, Uwe; Wohllebe, Arabel (International Journal of Interactive Mobile Technologies (iJIM), 2021)
With digitization and the spread of smartphones in many areas of life, mobile devices have also become increasingly relevant in education. While comprehensive research exists especially for smartphone use among teenagers and students, the findings for elementary school students are limited. Based on a survey, this case study provides exploratory insights into the smartphone usage behavior of elementary school students in a rural region in northern Germany. The responses of 33 students in grades 3 and 4 (ages 8 to 10) show that many students already own a smartphone at this age and use it daily, sometimes for several hours, especially for gaming and media consumption. The influence of owning an own smartphone on usage and leisure activities is reviewed. School use is of little relevance among the elementary school students surveyed.